History of education within graduate programs in education in Pará state universities - Miranda, Joaquina Ianca; Damasceno, Alberto; Mesquita, Jéssica; Madeira , Iza; Maia, Jamylle; Lobato, Vivian da Silva (Seven Editora, 2023)
This work has as its central theme the History of Education in Pará state within production from Graduate Programs of Education in the Federal University of Pará (PPGED/UFPA) and the Pará State University (PPGED/UEPA). The aim is to identify theme frequency among a total of published scientific works, as well as to check which thematic division and historic period discussions are aligned. The research was carried out through and quantitative-qualitative approach, and had systematic mapping as its technique, developing a state of knowledge on the History of Education in Pará. Results point out a majority of studies about the First Republic and the History of the Present Time in both Programs, also with reoccurring themes related to school education. It becomes evident there is a knowledge gap that may be filled for future research, as it is fundamental for education research, especially in Pará, to undergo developments to deepen works on the History of Education in this state.DOI:https://doi.org/10.56238/alookdevelopv1-035